Evaluación larvicida de suspensiones acuosas de Annona muricata Linnaeus «guanábana» sobre Aedes aegypti Linnaeus (Diptera, Culicidae) - Bobadilla, Miguel (2005)
The aim of the present study was to evaluate the larvicidal toxicity of aqueous suspensions from ethanol extracts of Annona muricata L. «custard apple» seeds, flowers, leaves, stem bark and root bark on fourth instar larvae of Aedes aegypti L. (Diptera: Culicidae) as well as to determinate susceptibility level . The highest larvicidal toxic effect was to the seeds suspension with 100% mortality at 0,5 mg/mL from 24 hours of exposure, and flowers suspension at 10 mg/mL from 48 hours of exposure and leaves suspension at 100 mg/mL from 36 hours of exposure. In seed suspension, lethal concentrations 50% (LC50) and 90% (LC90 ) values were 0,02 mg/mL and 0,11 mg/mL, in flowers suspensions were 3,33 mg/mL and 12,16 mg/mL, in leaf suspensions were 8,25 y 26,87 mg/mL and stem bark suspensions were 97,23 mg/mL, respectively. Log-dosage/probit lines indicated homogeneous responses towards the five aqueous suspensions, because of phytochemicals are distributed in each part of tree.